GENDER DOMINATION IN LOCAL NEWSPAPERS - Mariani Amri (Expose: Jurnal Ilmu Komunikasi, 2018)
This study was held at Fajar and Tribun Timur offices in Makassar. This research is describedthrough texts, discourse practice, and socio-cultural practice by using CDA (Critical Discourse Analysis) fromNorman Faircloughs’ model. The model includes textual level, discourse practice level, and socio-culturalpractice level. The type of this research is qualitative approach. This approach tries to get closer to what is beingstudied, that is gender domination in Fajar and Tribun Timur daily newspapers. It aims at in-depth and holisticunderstanding of gender domination in newspapers. Its flexibility is well suited to make interpretation todescribe the facts and the phenomena of gender in newspapers as the way they are based on the data found. Theresearch aims; to identify the domination of gender in Fajar and Tribun Timur daily newspapers, to analyse howgender dominations are expressed in those daily newspapers, and to analyse the effect of gender domination onnews stories in those newspapers. The result of this research shows that Fajar and Tribun Timur daily are stillmale dominated discourse in the news-making process which influences the news stories printed in thosenewspapers. Gender domination in Fajar and Tribun Timur daily newspapers as a discourse has been proven toaffect our views on news stories text, news stories production, and socio-cultural practices.